INTEGRATING LOCAL WISDOM IN LANGUAGE TEACHING - Arif Ma'mun Rifa'i (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2019)
AbstractThis paper aims to describe local wisdom integrated in language teaching. Currently, the demand of mastering English is undeniable, because the world to be aware of English as international language. Teaching English is not only as if teaching word, structure and pronunciation but also teaching English means teaching culture and the values contained in language. Exorbitant sadness for a local value to be lost because of foreign values, therefore, in language teaching in Indonesia needs variety of ways to filter from gnawing at foreign values. In fact, teachers may need some efforts and procedures in integrating local wisdom in English language teaching where as foreign language in Indonesia. The ways are: Local wisdom can be got from local area or district. Approach is category involving a set of assumptions dealing with the nature of language teaching, focusing on how to select texts or material which are suitable for use with the student. Materials include some points leastwise namely: achieve impact, help learners develop confidently, provide relevant content, expose learners to authentic use of language, provide opportunities for authentic language use, take into account individual differences, and encourage learners’ involvement. Reflective reflects what teachers did then developed for next cycles.Keywords : integrate, local wisdom, language teaching,